Taxation, Information, and Withholding : Evidence from Costa Rica - Brockmeyer, Anne; Hernandez, Marco (World Bank, Washington, DC, 2016)
This paper studies tax withholding on business sales, a widely used compliance mechanism which is largely ignored by public finance theory. The study introduces a withholding scheme, whereby the payer in a transaction collects tax from the payee, in a standard evasion model. If the taxpayer can fully reclaim the tax withheld, withholding is irrelevant to her evasion decision. If reclaim is costly, however, withholding establishes a compliance default. To show this empirically, the analysis exploits a ten-year panel of registration, income tax and sales tax records from 400,000 firms in Costa Rica, and over 20 million third-party information and withholding reports. The paper first documents the anatomy of compliance, providing novel measures of compliance gaps on the extensive, intensive and payment margins. It then shows that interventions leveraging the existing third-party information reduce these compliance gaps only marginally. Coverage by a withholding scheme, in contrast, is correlated with higher reported taxable income both across firms and within firms across time. Quasi-experimental estimations show that a doubling of the withholding rate leads to a 40 percent increase in tax payment among treated firms and a 10 percent increase in aggregate revenue. The mechanisms are incomplete reclaim of the tax withheld and reduced misreporting.